Muscular Activities Measurements of Forward Lean and Upright Sitting Motorcycling Postures via Surface Electromyography (sEMG) - Muhammad Izzat Nor, Ma'arof; Abdul Rahman, Omar; Rohani, Haron; Hazran, Husain; Muhammad, Abdul Wahab (EDP Sciences, 2017)
Motorcycling postures are generically speculated to be physical and physiologically demanding – which in-turn may lead to motorcycling fatigue, and then becoming a possible factor to road accident. The objective of this study was to measure the muscular activities of various motorcycling postures. High muscular activity reading will signifies that motorcycling is indeed physically and physiologically demanding to the motorcyclist. For this particular study, the following postures were tested: i) forward lean, ii) upright sitting, and iii) neutral sitting (as control). Surface electromyography (sEMG) measurement was conducted on the following muscles: i) extensor carpi radialis, ii) upper trapezius iii) latissimus dorsi, and iv) erector spinae. The results showed that for all test subjects, the muscular activities readings for the forward lean posture was actually close to neutral sitting’s. Whilst, the upright sitting had showed much higher muscular activities measurement instead. Conclusively, this study had proven that any types of discomforts associated with the forward lean posture is not originated from muscular activities. Whereas, confirming that any discomforts in regards to the upright sitting is indeed related to muscular activities. Further studies are warranted to discover the actual risk factors that causes physical and physiological discomforts for the forward lean motorcycling posture.